International society and its critics - Bellamy, Alex J. 1975- (Oxford University Press, 2005)
Leading scholars come together to evaluate the International Society approach to world politics. They demonstrate that a proper understanding needs to incorporate many types of actor and be able to explain the different types of issue in world politics such as terrorism, global governance and the role of international law.